Study Literature Review Artikel Terindeks Scopus Perihal Kebijakan Berkelanjutan Untuk Mengatasi Kemacetan Lalu Lintas - Nova Magdalena Ginting; Novi Eka Ratnasari (Universitas Padjadjaran, 2022)
A city without congestion is a form of support for the 11th sustainable development goal A city without congestion is a support for the achievement of the 11th Sustainable Development Goals (SDGs)